Perlindungan Hukum Terhadap Korban Phising Terkait Pengiriman File Apk - Artanti Zahra Adisa; Andriyanto Adhi Nugroho (JUSTISI, 2024)
Abstract: In Indonesia, technological advancements are undergoing rapid changes, and this can be beneficial for the daily needs of people. However, apart from the positive aspects of technology itself, there are also cyber threats present in society, for example, phising. Phising is a cybercrime that initially carried out by deceiving victims through the transmission of fake links. However, as it has evolved, phising is now conducted by sending files in apk format through Whatsapp. This research aims to determine the importance of legal regulations regarding phising cases in Indonesia. this study use the normative juridicial legal research as the research method. The results of this study indicate that current legislation in Indonesia doesn’t clearly regulate phising, and the Information and Electronic Transactions Law (UU ITE) doesn’t have specific articles addressing phising. Therefore, there is a need for Indonesia to enhance regulations concerning phising within the UU ITE or to develop separate legislation as a derivative of the UU ITE specifically addressing phising issues. Keyword: cybercrime; phising; cyber threats